Fluoride in dental plaque after a single toothbrushing with monofluorophosphate dentifrice - (:unkn) unknown (My University, 1990)
Many studies have shown that topical fluoride applications can produce a fluoride reservoir in dental plaque. Since the most common topical fluoride application is via toothbrushing with fluoridated dentifrices, the aim of this study was to measure fluoride uptake by dental plaque after a single toothbrushing with monofluorophosphate (MFP) toothpaste and to follow the plaque until its fluoride concentration returned to the prebrushing levels. In a fluoridated area, plaque samples were collected from 26 children who brushed with MFP toothpaste, 22 children who brushed with a fluoride-free control toothpaste, before brushing and at intervals of 10 minutes, 1 hour and 2 hours after brushing. A combination fluoride electrode was used to determine the fluoride content of the samples. In conclusion, our study has shown that brushing with fluoridated water has a positive effect on the fluoride level of the plaque and the addition of MFP did not make a significant change, although it had a short term effect. A negative correlation was established between plaque wet weight and its fluoride content whenever the plaque equilibrated.
Keywords: Female; Humans; Adolescent; Male; Child; Toothbrushing; Dental Plaque; Fluorides; Fluoridation; Phosphates; Toothpastes